PELATIHAN GAMIFIKASI DALAM PEMBELAJARAN: MENINGKATKAN KETERLIBATAN DAN PARTISIPASI SISWA SEKOLAH MENENGAH PERTAMA - H, Nurhikmah; Bena, Baso Asrul N.; Ramli, Abdul Malik; Mustafa, Mustafa; Sinaga, Andromeda Valentino (LP2M Universitas Ibrahimy, 2025)
The limited technological infrastructure in West Sulawesi challenges teachers in integrating technology into education, hindering interactive and engaging learning experiences. Gamification offers a solution by creating engaging learning environments with existing resources. A gamification training program at SMPN 1 Majene aimed to enhance junior high school teachers' skills in applying gamification to improve student engagement and participation. Before the training, most teachers were familiar with gamification through social media, but few understood its educational context. Despite the unstable internet, teachers had sufficient computer skills and showed enthusiasm for gamification. The program included sessions on gamification principles and practical applications using platforms like Wordwall and Genialy. Post-training evaluations revealed significant improvements in teachers' knowledge and skills. All participants felt confident and prepared to implement gamification, with most reporting enhanced abilities in designing gamified lessons. The training effectively addressed infrastructure limitations, enabling teachers to create interactive, motivating, and engaging learning experiences, ultimately improving teaching quality and student participation in the classroom.